No Fear Coding : Computational Thinking Across the K-5 Curriculum - Williams, Heidi (Book collections on Project MUSE., 2021)
This book shows K-5 educators how to bring coding into their curriculum by embedding computational thinking skills into activities for every content area, helping students prepare for coding in middle grades as they build knowledge. Features classroom-tested lessons and activities designed for skills progression, ready-to-implement coding exercises, and case studies and explorations of technology tools and resources. This edition offers new research, updated tools and more.